2014
DOI: 10.2337/dc14-0920
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and Risk of Cardiovascular Disease and All-Cause Mortality in Insulin-Treated People With Type 1 and Type 2 Diabetes: A Cohort Study

Abstract: OBJECTIVEHypoglycemia has been associated with an increased risk of cardiovascular (CV) events and all-cause mortality. This study assessed whether, in a nationally representative population, there is an association between hypoglycemia, the risk of CV events, and all-cause mortality among insulin-treated people with type 1 diabetes or type 2 diabetes. RESEARCH DESIGN AND METHODSThis retrospective cohort study used data from the Clinical Practice Research Datalink database and included all insulin-treated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
210
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(225 citation statements)
references
References 31 publications
7
210
3
5
Order By: Relevance
“…Investigators et al, 2013, Khunti et al, 2015, Majumdar et al, 2013, McCoy et al, 2012, Zhao et al, 2012, Zoungas et al, 2010. Despite the heterogeneity, we note that direction of association was consistent across all the studies in the Forest plot.…”
Section: Association Between Hypoglycaemia and Mortality (Figure 3)supporting
confidence: 57%
See 4 more Smart Citations
“…Investigators et al, 2013, Khunti et al, 2015, Majumdar et al, 2013, McCoy et al, 2012, Zhao et al, 2012, Zoungas et al, 2010. Despite the heterogeneity, we note that direction of association was consistent across all the studies in the Forest plot.…”
Section: Association Between Hypoglycaemia and Mortality (Figure 3)supporting
confidence: 57%
“…We screened 1273 citations and included 17 studies with a total of 1498358 participants in the meta-analysis (Bonds et al, 2010, Chiba et al, 2015, Duckworth et al, 2011, Hsu et al, 2013, Origin Trial Investigators et al, 2013, Johnston et al, 2012, Johnston et al, 2011, Khunti et al, 2015, Majumdar et al, 2013, McCoy et al, 2012, Rajpathak et al, 2015, Rathmann et al, 2013, Signorovitch et al, 2013, Zhao et al, 2012, Zoungas et al, 2010. The flow chart of the study selection in shown in the supplementary eFigure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations